Efecto de factores clínicos, bioquímicos y genéticos sobre el desarrollo y progresión de la nefropatía diabética en una población mexicana con diabetes mellitus tipo 2 - Ortega Pierres, Luz Elena (Universidad Michoacana de San Nicolás de Hidalgo, 2005)
In the last decades, the type 2 diabetes (DM-2) has had an alarming increment in its incidence and prevalence in the worldwide and in Mexico, especially in the Mexican-American population. The genetic predisposition for kidney damage in the patient with DM-2 is the final result of the accumulative effect of multiple genetic and environmental factors. The renin-angiotensin system (RAS) components and its genes polymorphism represent an area of intense research for the kidney disease. OBJECTIVE. Determine if there is an association between the D/D genotype of the angiotensin-converting enzyme (ACE) gene, the serum concentration of the enzyme and the development of diabetic nephropathy in patients with DM-2 in a Mexican population. MATERIALS AND METHODS. A cross-sectional, case-control study was carried out. 240 patients were recruited, both sexes, with age > 30 years old with DM-2 who represented the study group and 230 healthy subjects, both sexes, who were taken from three prior studies that were made in the Investigation Unit from the Mexican Institute of Social Security (IMSS) Mexico, without DM-2 called control group. Glucose, creatinine, cholesterol, triglycerides, c-LDL, c-HDL and ACE were measured in serum. The glomerular filtration rate (GFR) was calculated. The ACE gene polymorphism was determined.

En las últimas décadas, la diabetes mellitus tipo 2 (DM-2), ha tenido un alarmante incremento en su incidencia y prevalencia en todo el mundo y en México, especialmente en la población México-americana. La predisposición genética para daño renal en el paciente con DM-2 parece ser el resultado del efecto final acumulativo de múltiples factores genéticos y ambientales. Los componentes del sistema renina-angiotensina (SRA) y los polimorfismos en sus genes son un área de intensa investigación de asociación para la enfermedad renal. OBJETIVO. Determinar si existe asociación entre la presencia del genotipo D/D del gen de la enzima conversora de angiotensina (ECA), su concentración sérica y el desarrollo de nefropatía diabética en pacientes con DM-2 en una población Mexicana. MATERIALES Y MÉTODOS. Se realizó un estudio transversal, de casos y controles. Se incluyeron 240 sujetos mayores de 30 años, de ambos sexos, con DM-2, que constituyeron el grupo de estudio, y 230 sujetos sanos tomados de tres estudios previos de la misma línea de investigación del Instituto Mexicano del Seguro Social (IMSS) sin DM-2, que fue el grupo control. Se midió en suero glucosa, creatinina, colesterol, triglicéridos, c-LDL, c-HDL y ECA. Se calculó la tasa de filtración glomerular (TFG).
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias en Farmacología Básica
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2005-0001; Factores; Bioquímico; Genético; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2875